The dark side of transformational leadership a critical perspective - Dennis Tourish (New York Routledge, 2013)
Introduction : why the dark side? Why now? -- Transformational leadership : the dynamics of excessive leader agency -- Coercive persuasion, power and corporate culturism -- Spirituality and leadership : using ideology to enhance leaders' power -- The dark side of leadership and silence in the workplace -- The folly and the dangers of leadership education in business schools -- The dark side of leadership in corporate America : Enron revisited -- The militant tendency's long march to oblivion: conformity and authoritarian -- Leadership on the left -- Leadership, group suicide and mass murder : Jonestown and Heaven's Gate through -- The looking glass -- Accounting for failure : bankers in the spotlight -- Reimagining leadership and followership : a processual, communication perspective.
Includes bibliographical references and index.
Keywords: Transformational leadership